2011
DOI: 10.1111/j.1750-3841.2011.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet and Far Infrared Radiation on Microbial Decontamination and Quality of Cumin Seeds

Abstract: This research attempts to apply UVC and far infrared (FIR) radiation for pasteurization of cumin seeds. The data suggested that combined UVC and FIR radiation treatments can become a promising new method for pasteurization of cumin seeds without causing any detrimental defect to the quality parameters. The results of this industry partnered (Kadioglu Baharat, Mersin, Turkey--http://www.kadioglubaharat.com) study were already applied in industrial scale production lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…A review of the literature shows that there have been only a few studies relevant to the effect of UV-C irradiation on spices. Erdoǧdu and Ekiz (12) reported that the use of UV-C irradiation alone on cumin seeds for 60 min reduced total aerobic bacteria by about 0.6 log unit, and extending the UV-C application up to 120 min did not offer any additional reduction. As these results indicate, the effects of UV-C and NIR treatments alone were not effective in reducing the number of pathogens found in agricultural spices while maintaining product quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature shows that there have been only a few studies relevant to the effect of UV-C irradiation on spices. Erdoǧdu and Ekiz (12) reported that the use of UV-C irradiation alone on cumin seeds for 60 min reduced total aerobic bacteria by about 0.6 log unit, and extending the UV-C application up to 120 min did not offer any additional reduction. As these results indicate, the effects of UV-C and NIR treatments alone were not effective in reducing the number of pathogens found in agricultural spices while maintaining product quality.…”
Section: Discussionmentioning
confidence: 99%
“…As none of these methods has proved to be completely satisfactory, searches for safe and efficient control methods, including investigations into the use of infrared (IR) heating and UV irradiation, for decontamination of dried spices are being undertaken (10,11,12). IR radiation is part of the electromagnetic spectrum, with wavelengths between those of UV and microwave radiation, and is distinguished as near IR (0.76 to 2 m), medium IR (2 to 4 m), and far IR (4 to 1,000 m).…”
mentioning
confidence: 99%
“…In a study conducted with red pepper, it was found that UV‐C application at 4 J/cm 2 dose did not cause a significant change in the L *, a *, and b * values of the samples (Cheon et al, ). In another study, Erdoğdu and Ekiz () studied the combination of far infrared (200, 250, and 300°C and 4.8, 28, and 1.57 min, respectively) and UV‐C application (75.6 J/cm 2 ) for cumin. Similar to our results, they found L * and b * values were not significantly affected UV‐C application at a dose of 75.6 J/cm 2 while a * value had a significant decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation is the most used decontamination technique, which is very effective in microbial inactivation, but it has disadvantages such as oxidation of aromatic components, poor consumer acceptance, and requirement for special facility with high cost (Sadecka, 2007;Variyar, Gholap, & Thomas, 1997). Because of these limitations, many researchers have studied alternative methods such as pulsed electric field (Keith, Harris, Hudson, & Griffiths, 1997), infrared heating (Eliasson, Libander, Lövenklev, Isaksson, & Ahrné, 2014;Staack, Ahrné, Ahrné, Borch, & Knorr, 2008), remote plasma (Hertwig et al, 2015), pulsed UV light (Fine & Gervais, 2004;Nicorescu et al, 2013;Sharma & Demirci, 2003), cold plasma (Kim, Lee, & Min, 2014), and combination of far infrared and ultraviolet (UV-C) radiation (Erdoğdu & Ekiz, 2011 ), gamma irradiation under modified atmosphere packaging (Kirkin, Mitrevski, Gunes, & Marriott, 2014) and combination of UV-C radiation and mild heat treatment (Cheon, Shin, Park, Chung, & Kang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…IR heating has produced promising results for the surface pasteurization of black pepper seeds (Erdoğdu and Ekiz ), as well as for cumin seeds if combined with ultraviolet treatment (Erdoğdu and Ekiz ). Furthermore, Staack and others () found that IR treatment efficiently decontaminated B. cereus spores in paprika powder.…”
Section: Introductionmentioning
confidence: 99%